Multifunctional resource room: A tool in the teaching and learning process for students with disabilities in regular Secondary Education (Research, Society and Development, 2025)
This research aimed to analyze the contributions of the Multifunctional Resource Room (SRM) to the teaching and learning process of students with disabilities in a public school in the state education system of Roraima. This work is justified by the importance and need for reflection and understanding of the main interventions in the learning of students in Multifunctional Resource Rooms with specialized educational support. Most of the students with disabilities enrolled in the SRM have intellectual disabilities. This is a qualitative-quantitative research study using Action Research and Hermeneutic methods. Content Analysis and Bibliographic Analysis were used for data analysis. The research was conducted at the Ayrton Senna State School, located in Boa Vista, the capital of the state of Roraima. The target population consisted of 76 high school teachers and assistants working in the Multifunctional Resource Room and providing Specialized Educational Support; from these, 2 teachers from the Specialized Educational Support room and 11 assistant teachers were used as a sample. The school was chosen randomly. It is concluded that the inclusion process has long sought a new understanding of the included person. It can be observed that there is improvement in a new reflection on the inclusion process, promoting new thinking and action. The teachers in the multifunctional resource room contribute to the student's development and significantly influence the student's physical, social, and intellectual development.